GIS-Based Method for Finding Optimal Ocean Energy Location: A Case Study of Terengganu State - Shafiai, S.H.B. (Institute of Physics Publishing, 2020)
Ocean energy is one of the most important renewable energy sources and it can highly contribute to the supply of the world's electricity demands. This paper presents a method of locating the highest potential sources of ocean energy by implementing Geographic Information System (GIS). The aim of this study was to find the optimal wave energy location in the coastal area of Terengganu state in Malaysia. The wave data for the years 2015-2017 have been collected. The GIS was adopted to prepare data for analysis and perform geostatistical analysis. The results showed the exact location of areas in the coastal area of Terengganu in which maximum energy from the ocean can be harvested. The proposed methodology can be applied in other coastal areas. Â© Published under licence by IOP Publishing Ltd.